Students’ experience in the teaching and learning of English amid the covid-19 outbreak - Sabariah Abd Rahim (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
The Covid-19 has caused educational institutions to shut all across the world. As a result, the teaching and learning methods have changed drastically. Teaching on digital platforms has now become the trend, and whether it is language apps, virtual tutoring, or video conferencing tools, there has been a significant rise in usage since Covid-19. With this, the study investigated students’ experience in their use of ICT during the Malaysia Movement Control Order (MCO) Phase 1. 120 students were asked to respond to a Google Form questionnaire shared in WhatsApp. However, only 98 students had responded to the questionnaire. In general, the finding shows that the students have limited access to the internet, and due to this limitation, they prefer to have downloadable videos and lecture presentation slides that they can access at any time asynchronously. This study has implications on the facilitating of classroom practice during the pandemic Covid-19.